The Key Advantages and Disadvantages of Matrix Organizational Structures - Krzysztof Goś (Studia i Materiały)
The article is a review of the literature on the key advantages and disadvantages of matrix organizational structures. After providing a brief introduction into the discipline, it identifies and discusses eight major characteristics of matrix organizations. In the reviewed publications, three characteristics are considered primarily as advantages of matrix structures, one as a disadvantage, whereas the four remaining arouse controversies as to their beneficial or negative nature. The controversial characteristics are indicated as a field for further investigation.